A Visual Basic Software For Computing of the One Dimensional Heat Equation by Using B Spline Solution - Çağlar, Hikmet; Çağlar, Nazan; Özer, Mehmet; CUHACI, LEVENT (My University, 2009)
Microsoft Visual Basic® has been used for developing a software for the one- dimensional heat equation. We have solved the equation by means of a computer and developed user-friendly software with a graphical user interface. The numerical solution of the equation is visually illustrated. The software does not require familiarity with any new environment and is highly flexible; it can also easily be adapted to other experimental methods.